2015
DOI: 10.1111/jphp.12452
|View full text |Cite
|
Sign up to set email alerts
|

Development of an insect metalloproteinase inhibitor drug carrier system for application in chronic wound infections

Abstract: This study reports the development of a poloxamer hydrogel as a suitable carrier system for the application of IMPI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…[2,5] We found that IMPI, a metalloprotease inhibitor from G. mellonella, inhibits an important P. aeruginosa virulence factor, the metalloproteinase PE, [1] as well as other M4 metalloproteases. [28,29,31,36] A GST fusion tag does not affect the activity of native IMPI, [32] allowing us to produce a functional recombinant IMPI fusion protein in E. coli which showed a stable and batch-independent ability to inhibit thermolysin and purified PE, with a steeper descent than that of the chemical inhibitor phosphoramidon (Figure 1). IMPI is more specific and more potent than other PE-inhibitors [28] such as those based on hydroxamate, [37] metal-chelating dipeptides, [38][39][40] or small molecules.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2,5] We found that IMPI, a metalloprotease inhibitor from G. mellonella, inhibits an important P. aeruginosa virulence factor, the metalloproteinase PE, [1] as well as other M4 metalloproteases. [28,29,31,36] A GST fusion tag does not affect the activity of native IMPI, [32] allowing us to produce a functional recombinant IMPI fusion protein in E. coli which showed a stable and batch-independent ability to inhibit thermolysin and purified PE, with a steeper descent than that of the chemical inhibitor phosphoramidon (Figure 1). IMPI is more specific and more potent than other PE-inhibitors [28] such as those based on hydroxamate, [37] metal-chelating dipeptides, [38][39][40] or small molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Given the potential of IMPI for the treatment of P. aeruginosa infections, we produced a recombinant insect metalloproteinase inhibitor‐glutathione‐S‐transferase (IMPI‐GST) fusion protein in Escherichia coli and tested its ability to inhibit the M4 metalloproteinases thermolysin and PE, as well as the P. aeruginosa secretome (Sec). We investigated the influence of Sec on skin cells and in vitro and ex vivo porcine wound models using a thermosensitive hydrogel for IMPI application . Finally, we tested the ability of IMPI‐GST to restore the viability and migration capacity of Sec‐treated keratinocytes and to prevent necrosis in a porcine wound model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prime example is the development of AMPs from medicinal maggots of L. sericata which are formulated in hydrogels to test the efficacy of synthetic counterparts in wound dressings and as cosmetic ingredients to deter dermatological pathogens [ 21 , 104 , 119 ]. Other insect-derived AMPs such as the IMPI from G. mellonella [ 120 ] are currently also being developed for the therapy of chronic wounds [ 121 ]. Further promising medicinal applications of insect-derived AMPs are currently being explored in therapies to cure eye, lung and urogenital infections [ 117 , 122 , 123 ].…”
Section: Activity Screening and Medical Applications Of Insect Antimimentioning
confidence: 99%
“…Peptides are good candidates for controlling wound infections. A drug carrier system was designed for delivering an insect metalloproteinase inhibitor (IMPI) drug to enable treatment of chronic wound infections [58]. Poly(lactic-co-glycolic acid) (PLGA) supplies lactate that accelerates neovascularization and promotes wound healing.…”
Section: Delivery Of Peptidesmentioning
confidence: 99%